Energy Optimization in Cloud Computing: A Review - Pandey, Ashish Kumar; Ahmad, Shish (International Journal of Computer Sciences and Engineering, 2019)
Nowadays, modern computing environment, having lots of challenges towards flexibility and processing capabilities. So Data Centers are required. Each data center provides physical wires by which enormous compute, network and storage resources are connected. Data centers are responsible for computation, space, network points and their effective and efficient operations. Therefore, enhancing the performance of the system likes total productivity, reliability and availability having the requirement to minimize the energy consumption of Data Centers. So, energy Consumption reductions are not only to enhance the system performance but also optimize the cost. Thus, an energy optimization is becoming a challenging task due to speedy growth in data and computing applications. In this paper we critically studied about the different energy based proposed methods and comprehensive survey along with a taxonomy of network topologies, either used in commercial data centers, or proposed by researchers.